Where did dinosaurs go? - Unwin, Mike.; Robinson, Andrew; Goffe, Toni; Smith, Guy (London ; Usborne : Tulsa, OK : EDC, 1991)
Supplies many interesting facts about what dinosaurs were like, how they lived, and what may have happened to them.
Includes index.
4.5
K-3
K-3
Keywords: Dinosaurs -- Juvenile literature; Dinosaurs; Dinosaurs